(untitled) (Research, Society and Development, 2023)
With the advancement of medicine and health care, life expectancy has increased considerably. Thus preventing, delaying and attenuating the signs of aging has become inevitable. The lips are highlighted on the face and show youth when they are hydrated and full. Young patients, still without loss of structure, seek to modify anatomical characteristics in search of perfect lips. Filling with hyaluronic acid (HA) is the most suitable procedure for this purpose. Biocompatible, temporary, reversible and safe when performed by a qualified professional. Knowledge of the general anatomy of the face, the material of choice and the appropriate technique is necessary for the professional to identify, intervene and remedy possible intercurrences. This work reviews the literature on the complications and intercurrences caused by HA as lip fillers and their treatments when necessary. The purpose of this paragraph is to introduce the importance of lip fillers with hyaluronic acid (HA) as a popular aesthetic procedure to improve the appearance of the lips. The relevance of knowledge of facial anatomy, the appropriate technique and the correct choice of material to avoid complications and intercurrences are highlighted.